REFLEKSI NILAI-NILAI KEAGAMAAN PADA ARTIKEL REPUBLIKA “SILATURAHMI EDISI JULI 2016” - Wardah Hanafiah (Epigram, 2019)
AbstractThis study aims to determine the religious values contained in the text in the article entitled “Silaturahmi” which is published in the “Republika” online mass media in the “Khazanah Rubric”. These religious values are taught as part of the development of character education. Data is taken from article texts that contain good teaching values. This research is a qualitative research using content analysis method. Research data analysis techniques use triangulation. The research findings show that the religious values contained in the article entitled "Gathering" are twofold, namely the value of friendship and brotherhood. The value of friendship teaches someone to care for each other and help others or friends who are in trouble. While the value of brotherhood refers to the building of the character of belonging and togetherness. Of the two religious values, it also teaches the reader how the values of friendship and brotherhood are as a guide for socializing in community life.Keywords: Religious Value, Online Media, ArticlesAbstrakPenelitian ini bertujuan untuk mengetahui nilai-nilai keagamaan yang terkandung didalam teks pada artikel berjudul Silaturahmi yang dimuat pada media massa online Republik dalam Rubrik Khazanah. Nilai-nilai keagamaan tersebut diajarkan sebagai bagian dari pembangunan pendidikan karakter. Data diambil dari teks-teks artikel yang mengandung nilai ajaran kebaikan. Penelitian ini merupakan penelitian kualitatif menggunakan metode analisis isi. Teknik analisis data penelitian menggunaan triangulasi. Temuan penelitian menunjukkan bahwa nilai keagamaan yang terkandung didalam artikel berjudul ‘Silaturahmi’ ada dua, yaitu nilai persahabatan dan persaudaraan. Nilai persabatan mengajarkan pada seseorang untuk saling peduli dan membantu orang lain atau teman yang sedang kesulitan. Sedangkan pada nilai persaudaraan merujuk pada pembangunan karakter saling memiliki dan kebersamaan. Dari kedua nilai keagamaan tersebut mengajarkan pula pada pembaca bagaimana nilai persahabatan dan persaudaraan tersebut menjadi pedoman dalam bersilaturahmi dalam kehidupan bermasyarakat.Kata kunci: Nilai Keagamaan, Media Online, Artikel